Морозостойкость рекомбинантно-инбредных линий пшеницы и ее связь с аллелями микросателлитных локусов - Галаева, М.В.; Файт, В.И.; Галаев, А.В.; Федорова, В.Р.; Сиволап, Ю.М. (Фактори експериментальної еволюції організмів, 2014)
Aim. The study of the relation between allelic differences of microsatellite loci and frost resistance of recombinant-inbred lines Luzanovka odesskaya/Odesskaya krasnokolosaya. Methods. Polymerase chain reaction (PCR), gel-electrophoresis, test of frost resistance. Results. Microsatellite analysis of chromosomes of homeologous group 5 and the analysis of frost tolerance were performed on recombinant-inbred lines (RILs) derived from a cross between winter wheat varieties Luzanovka odesskaya (tolerant to frost) and Odesskaya krasnokolosaya (susceptible to frost). Microsatellite analysis of parental varieties by using 7 microsatellite markers located on chromosomes 5А, 5В and 5D showed polymorphism for loci Xbarc 117-5A, Xwmc75-5В and Xgpw3191-5B. These microsatellite markers were used for analysis of RILs. The association between allelic differences at microsatellite loci and frost resistance was studied. Conclusions. Allelic differences of RILs Luzanovka odesskaya/Odesskaya krasnokolosaya for Xgpw3191-5B locus showed a significant relationship with the level of frost resistance. Increase of frost resistance of lines at the germination stage by 11–17% was associated with 178 bp allele for this microsatellite locus, which is typical for the frost resistant variety Luzanovka odesskaya. Increase of frost resistance of lines at the tillering stage was associated with 236 bp allele, which is typical for the variety Odesskaya krasnokolosaya.